Mental Health Issues Among Adolescents: Challenges and Management - Kumar, Saurabh; Kumar, Krishan; Avti, Pramod K; Anand, Akshay (Current Psychiatry Research and Reviews, 2025)
Adolescence is an important stage of life between childhood and adulthood. The shift in lifestyle, physical inactivity, high expectations of family/friends/teachers, and continuous exposure to social media and the internet have created physical, social, emotional, and mental imbalances in adolescents. The individuals of this age group are vulnerable and exposed to these stressful factors, leading to psychological complications. Most psychological problems diagnosed in the later stages of life begin in adolescence. The purpose of this mini-review was to identify mental health problems and available non-pharmacological interventions to manage the overall well-being of adolescents. A literature search was conducted to identify relevant studies, including research, review, and other articles/data available on PubMed, Google Scholar, ScienceDirect, WHO, GHDx, and AACAP. Search keys included essential keywords like adolescence, yoga, mental health, anxiety, depression, and a combination of these words. The literature search identified several mental disorders like emotional, behavioral, identity, psychosis, dietary, and other risky behaviors. Most of the non-pharmacological interventions adopted focused on improving the mental and physical well-being in school and community settings. Among all the interventions, we found yoga to be the most popular and widely accepted effective tool that reduces anxiety, depression, and psychological problems. Yoga also improved resilience, attention, and other well-being parameters. Yoga helps manage physical and mental health in adolescence.
Keywords: mental health